Walking Seattle : 35 tours of the Jet City's parks, landmarks, neighborhoods, and scenic views - Humphrey, Clark (Wilderness Press, an imprint of AdventureKEEN, 2018)
Grab your walking shoes and become an urban adventurer. Clark Humphrey guides you through 35 unique walking tours in the comprehensive guidebook. Go beyond the obvious mansions, postmodern palaces, and outdoor art. Soak up Seattle's history, parks, and vibe. Wander wide boulevards, narrow cobblestone lanes, and pedestrian pathways to Pioneer Square, Queen Anne Hill, the University of Washington campus, Foster Island, and beyond.